Association between red cell distribution width and tumour stage in patients with resected cancer of the head of the pancreas - Pradeep, Archana; Rameshan, Anjana; Krishna Kumar, Anjali Nair; George, Leyanna Susan (International Journal Of Community Medicine And Public Health, 2020)
Background: Predicting the clinical outcome in pancreatic cancer is often challenging due to the lack of reliable and cost effective prognostic parameters. Red Cell Distribution Width (RDW), an index of the variability in the size of the circulating RBCs has been reported to have prognostic significance in some malignancies. There is a scarcity of literature supporting its relevance in pancreatic cancer. Objective was to study the association between RDW and tumor stage in patients with pancreatic cancer attending a tertiary care hospital in South India and to correlate RDW and survival after surgery for pancreatic cancer. Methods: Retrospective analysis of prospectively collected digital medical records of 254 pancreatic cancer patients, who had undergone surgery at a tertiary centre between 2002 and 2015. This was supplemented with data obtained from telephone conversations with the patients and/or their next of kin. Results: Higher RDW values were associated with advanced tumor stages 84.2% of patients with stage 3 cancer and 92.3% with stage 4 cancer had high RDW values. High values were significantly associated with lower survival. The mean duration of survival for people with normal values was 83 months while that for patients with higher values was significantly lower at 72 months. Conclusions: There appears to be a significant association between RDW and tumor stage in pancreatic cancer. RDW also correlates with the duration of survival in pancreatic cancer patients. Thus, it may be useful in predicting the clinical outcome in pancreatic cancer.